ESTIMASI MEDIA ONLINE DALAM PROSES BISNIS PEMASARAN DAN JASA DI KOTA TASIKMALAYA MENGGUNAKAN METODE DISCRETE - Iskandar, Iqbal Dzulfiqar (LPPM Universitas Nusa Mandiri, 2019)
Online media is used by many organizations as a helping tool to reach the goal in the business process especially marketing or introducing a product that is marketed. Therefore, this research is trying to explain how massive the role of online media is, in the business process in the town of Tasikmalaya based on a statistic number scale from the data that refer to quantitative methodology, Discrete Data, and Correlational analyses method. Meanwhile. The result of this research reveals Online media is, towards business process marketing and service in the town of the Tasikmalaya area positively affected business process marketing and service. These results are supported by the results of data processing. From 78 organizations, the positive rate of online media on marketing and services is 95% greater than the positive level, which is only 5%. sig. (2-sided) of 0,000, meaning that α=0.05 is greater than the value of Sig. (2-sided) or [0.05> 0,000]. This shows that the variable X has an influence on variable Y. The results of the analysis of bivariate people, obtained the final value r =1, for the estimated value. This number defines the variable X which has a very strong attachment relationship to a variable.